2022
DOI: 10.7759/cureus.21977
|View full text |Cite
|
Sign up to set email alerts
|

Mild Abdominal Trauma Complicated With Bowel Perforation in Patient With Crohn’s Disease: Clinical and Intraoperative Findings

Abstract: Crohn's disease (CD) is a chronic inflammatory disease and is an autoimmune disorder. Due to its remission and relapse cycle, the integrity of the intestinal wall becomes compromised in patients with inflammatory bowel disease. This increases susceptibility to bowel perforation following mechanical injury, especially in patients using immunosuppressive therapy. However, few reports discuss the severity of injury after abdominal trauma in Crohn's patients and how much mild abdominal blunt trauma in such patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…It has been reported that relatively minor trauma in patients with CD can result in gastrointestinal injury. To the best of our knowledge, only 11 cases of traumatic intestinal injury have been reported [7][8][9][10][11][12][13][14][15]. All cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that relatively minor trauma in patients with CD can result in gastrointestinal injury. To the best of our knowledge, only 11 cases of traumatic intestinal injury have been reported [7][8][9][10][11][12][13][14][15]. All cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Crohn’s disease may be considered more prone to spontaneous intestinal perforation rather than normal population because of the associated chronic intestinal inflammation and friability as well as their requirement for immunosuppressive medications ( 2 ). However, spontaneous intestinal perforation remains a rare occurrence among them, accounting for 1–3% of all spontaneous intestinal perforation ( 3 , 4 ). The diagnosis of intestinal perforation can be commonly missed in CD patients ( 5 ).…”
Section: Introductionmentioning
confidence: 99%